THE ROLE OF TRANSESOPHAGEAL OVERDRIVE PACING IN TERMINATING PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA - Quốc Cường, Trương; Quang Khanh, Trương; Thị Hồng Nhung, Nguyễn; Nguyễn Quan Huy, Ngô; Duy Mẫn, Huỳnh (Journal of Health and Aging, 2025)
Transesophageal overdrive pacing is an accepted method for the diagnosis and treatment of paroxysmal supraventricular tachycardias, although is not used frequently in clinical practice. We describe four complex cases of paroxysmal supraventricular arrhythmia to review the role of transesophageal overdrive pacing in the interruption of paroxysmal supraventricular tachycardia. In these cases depend on clinical features such as pregnancy, resistance to antiarrhythmic drugs, and comorbid bradycardia that make it difficult to treat. These cases were successfully converted by transesophageal overdrive atrial pacing. Transesophageal overdrive atrial pacing is a low-cost, simple and safe procedure that can be performed at the bedside and can do many times, especially in patients, whose condition makes difficult the usage of medicines.